Friction effects during open-die micro-forging/extrusion processes : an upper bound approach - Ghassemali, Ehsan (2015)
In microforming processes it is preferred to not to use lubricants, due to their complex behavior in micro-scale. Nevertheless, using lubricants could increase the life time and decrease the required forming load. Thus, it is necessary to study and develop an analytical solution for different lubrication conditions in microforming processes. A previously studied upper bound model was modified in this study for various lubrication conditions in an open-die micro-forging/extrusion process. Two approaches were chosen for identifying the friction factor in the model: (i) global friction factor, (ii) localized friction factor. Comparison of the modeling results with the experimental showed the reliability of the second approach, providing a better fit.